Penyelesaian Vehicle Routing Problem Dengan Algoritma Clarke And Wright Savings Di Perumahan Umum Bulog Medan Amplas - Nurul Aina; James Piter Marbun (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
Distribution routes are generally a problem for every company, including in the public company BULOG Medan Amplas. Distribution to the Medan Amplas BULOG public company, namely having to serve every stall that is far from the warehouse with scattered locations, and limited vehicle capacity. So far, driver considerations in distributing products have only been based on random intuitions of driver and does not consider the efficiency of the route taken. Therefore, this research uses Clarke and Wright Savings algorithm to obtain optimal mileage by taking into account every consumer demand and vehicle capacity. Calculation results using the Clarke and Wright Savings Algorithm obtained the vehicle mileage of 695.08 km with a savings of 11 km or 1.56%.